2019
DOI: 10.1016/j.bbmt.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot, Exploratory, Randomized, Phase II Safety Study Evaluating Tumor Cell Mobilization and Apheresis Product Contamination in Patients Treated with Granulocyte Colony-Stimulating Factor Alone or Plus Plerixafor

Abstract: Because of the potential risk of tumor cell mobilization with granulocyte colony-stimulating factor (G-CSF), it is crucial to evaluate any potential effect of plerixafor treatment in the presence of G-CSF on multiple myeloma (MM) cell mobilization. This was an open-label, multicenter, randomized, exploratory, safety study (NCT01753453) that investigated the extent of MM cell mobilization after treatment with G-CSF + plerixafor in patients who were deemed poor mobilizers of hematopoietic stem cells. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, a major concern in the mobilization of stem cells for transplantation is the potential risk of tumor cell mobilization. In this respect, a recent study reported that MM tumor cells were not detected in the apheresis products of patients who received either G-CSF + P or those who received G-CSF alone [20]. Collectively, the findings from these two studies further support the safety of G-CSF + P for mobilizing CD34+ cells for transplantation in poor mobilizers.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, a major concern in the mobilization of stem cells for transplantation is the potential risk of tumor cell mobilization. In this respect, a recent study reported that MM tumor cells were not detected in the apheresis products of patients who received either G-CSF + P or those who received G-CSF alone [20]. Collectively, the findings from these two studies further support the safety of G-CSF + P for mobilizing CD34+ cells for transplantation in poor mobilizers.…”
Section: Discussionmentioning
confidence: 71%
“…2006 MM G-CSF SD; G-CSF SD + Plerixafor SD The Plerixafor group showed significantly higher rate of achieving optimal target ( P < 0.001)* and higher CD34 + cells collected Matsue et al [ 48 ] Phase 2 RCT, open-label, multicenter Nov. 2014–Mar. 2016 NHL G-CSF SD; G-CSF SD + Plerixafor SD The Plerixafor group showed higher rate of achieving optimal target Nahi et al [ 50 ] Phase 2 RCT, open-label, multicenter NA MM G-CSF SD; G-CSF SD + Plerixafor SD The Plerixafor group showed higher CD34 + cells yield Ri et al [ 55 ] Phase 2 RCT, open-label, multicenter Oct. 2014–Jul. 2015 MM G-CSF SD; G-CSF SD + Plerixafor SD The Plerixafor group showed higher rate of achieving optimal target Zhu et al [ 66 ] Phase 3 RCT, double-blind, multicenter Apr.…”
Section: Resultsmentioning
confidence: 99%
“…For example, multiple myeloma patients were studied where HSCs were mobilized with granulocyte colony-stimulating factor (G-CSF) to increase the numbers of mobile monoclonal plasma cells [ 11 ]. However, adding CXC-chemokine receptor 4 (CXCR4) antagonist, which blocks binding of CXC-chemokine ligand 12 (CXCL12), to G-CSF did not change the rate of cancer cell immobilization in multiple myeloma patients [ 12 ]. CXCL12 has been suggested to regulate most aspects of HSC maintenance, proliferation, localization, and self-renewal, which exists in cells that make up the niche within which these dormant cells reside [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vora [11] 1994 A pilot, exploratory, randomized, phase II safety study evaluating tumor cell mobilization and apheresis product contamination in patients treated with granulocyte colony-stimulating factor alone or plus plerixafor Nahi [12] 2019 CXCR4 is required for the quiescence of primitive hematopoietic cells.…”
Section: Yearmentioning
confidence: 99%